2018
DOI: 10.1093/hropen/hox030
|View full text |Cite
|
Sign up to set email alerts
|

The use of long-acting reversible contraceptives in Latin America and the Caribbean: current landscape and recommendations

Abstract: STUDY QUESTION Can the high rate and associated burden of unintended pregnancy (UP) and adolescent pregnancy in Latin America and the Caribbean (LAC) be reduced through wider access to and use of long-acting reversible contraceptive (LARC) methods? SUMMARY ANSWER Studies show that impoved access to and use of LARC methods is an effective tool for reducing the high rates of UP, unsafe abortion and abortion-related complications, and maternal deaths (as well as reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
0
14
0
11
Order By: Relevance
“…We believe that family planning programmes should give more attention to LARCs. The challenges to increase LARC uptake in Latin America and the Caribbean have been summarised by Bahamondes and colleagues 25 . These challenges include barriers of a subjective nature (misinformation, myths, and beliefs) and of an objective nature (institutional, service-related, training-related, cost-related, and others).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that family planning programmes should give more attention to LARCs. The challenges to increase LARC uptake in Latin America and the Caribbean have been summarised by Bahamondes and colleagues 25 . These challenges include barriers of a subjective nature (misinformation, myths, and beliefs) and of an objective nature (institutional, service-related, training-related, cost-related, and others).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to other studies that found common misconceptions about IUDs; including misconceptions that IUDs can puncture the womb, cause infertility, and be used to induce abortions. [ 2 , 3 , 6 , 17 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…IUDs have increased worldwide in popularity as a method of long-acting reversible contraceptives (LARC) [ 1 ]. Yet, in several developing countries such as in Latin America and the Caribbean the rate of use of LARCs (including IUDs) is < 10% [ 2 ]. According to a report published by the United Nations, 71.8% of married/in-union women aged 15–49 years in Jamaica in 2015 reported using contraceptives, but only 1.0% of these women reported using an IUD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Several analysts, for instance, have pointed out that the uptake of long-acting reversible contraceptives (LARCs) has been lower that could be expected given prevailing reproductive preferences and the evidence of LARCs’ safety and efficacy. 1 , 5 , 12 The high upfront cost of LARCs has been identified as an important barrier for this uptake. Evidence from recent experiences among adolescents in the US suggests that when financial barriers are removed, both LARC uptake and unintended pregnancy rates are favourably impacted.…”
Section: Introductionmentioning
confidence: 99%